What does a "universal mentality" mean? The response of St. Josemaría - García Huidobro, Joaquín (Mercurio Peruano, 2018)
Man, a being who lives on the surface, asks himself about the foundation; although he is particular, he seeks universality; although marked by finitude, he is open to infinity. The essay deals with the issue of access to the universal world, a question that is most important for theology and then an analysis of a text of St. Josemaría Escrivá is discussed, which refers to the need of Christians, especially the intellectuals, to form a universal mentality.